Ideologi Maskulinitas Dalam Film "Ngeri-Ngeri Sedap" Tahun 2022 - Ghifran Muhammad Baghiz; Pujiyanto Pujiyanto (MAVIS : Jurnal Desain Komunikasi Visual, 2024)
Media such as films are used to depict the reality of events in real life, such as conveying messages through characters. â€œNgeri-Ngeri Sedapâ€ is a film that tells the story of Pak Domu and his family from a Batak tribe background where they go through several conflicts. This research uses a descriptive-qualitative research method using purposive sampling of 8 scene samples from a total population of 129 scenes representing the storyline. Data collection methods include document studies as primary data and secondary data, namely direct observation studies, in-depth interview studies, and literature studies. Triangulation of source data from three expert sources was carried out to obtain validation. John Fiske's semiotic analysis (reality level, representative level, and ideology level) is used to obtain the form of masculinity in Pak Domu. The results of this research show that at the reality level, especially Pak Domu's codes of behavior, gesture, expression and way of speaking, with the representation level of camera, light, editing, music and sound codes, reconstruct the gender binary opposition ideology code of femininity which describe with dependency, weakness, subjectiveness, easily influenced, emotional, irrational, illogical, and indoor or domestic activities. The research result is found that masculinity ideology more prominent in the main character with indicators of relational power, being respected, control of emotionality, primacy of avoiding femininity, physical toughness/violence, self-reliance, and risk-taking.